Public mirror: legitimizing 'social' photography as a contemporary discipline - Gwaze, Alex (Centre for Film and Media Studies, 2019)
With all the public information about any famous person, topic or event 'googleable’ on the Internet, there seems to be nothing new for 'digital natives’ to discover other than the elusive Self. The Self is the 'new frontier’ and the smartphone camera is at the forefront of this quest, unearthing and exhibiting different kinds of content everyday. With over 95 million photographs and videos shared on Instagram daily; Photography has merged with social networking sites and applications (SNS/A) to become a recognisable phenomenon called – 'Social’ Photography. Despite its rich association with legitimate visual art-forms and numerous scholarly articles examining it’s various forms – the term 'Social’ Photography is unfamiliar to most. This inquiry discusses 'Social’ Photography in relation to existing literature to argue for its establishment as a legitimate discipline within the Creative Arts. By acknowledging its subjectivity and utilization of digital technologies, this study employed an interpretive group of methods and identified six characteristics of 'Social’ Photography – namely, (i) Activity, (ii) Participation, (iii) Identity, (iv) Glamour, (v) Protest, and (vi) Spectacle – that exemplify its capacity to curate a meaningful democratic public image. These six aspects can be used to categorize and formalize individual behaviour that can be analysed and interpreted to foster a better understanding of 'Social’ Photography as a discipline.